Deconstruction of Women’s Beauty Standard on Social Media: An Analysis - Syarifah, Ma’isyatusy; Nurjanah, Dewi Putri; Atikah, Nur; Syarif, Ahmad Zadul Ma’ad (Proceeding International Conference on Religion, Science and Education, 2022)
Women and beauty are identical entities. Beauty is considered a feminine trait and becomes a necessity that has been deeply rooted in the wider social system and is culturally indoctrinated, and has even become a trend on social media. Every day, women are haunted and convinced by the standardization of beauty, which increasingly plunges women into the praise of beauty. This also makes many social media accounts that take a lot of interest and profit by creating Instagram accounts that contain photos of beautiful women. This research highlights the deconstruction of women's beauty standards on social media, and how whether the post is an act of exploitation against women. A thorough qualitative method is used to examine social media especially Instagram which displays many photos of beautiful females. This study shows, first, the female beauty standard in social media mostly concerning beautiful and fashionable women. Second, the post on Instagram is an act of exploitation of women and is more concerned only with women’s beauty rather than women’s achievement.